The Translation of Laskar Pelangi into The Rainbow Troops - Ida Ayu Made Chintya Prema Saraswati; Julia Eka Rini (Kata Kita: Journal of Language, Literature, and Teaching, 2026)
This study examines the translation of metaphors in the Indonesian novel Laskar Pelangi (The Rainbow Troops) by Andrea Hirata and its English translation by Angie Kilbane. The primary objective of this research is to analyze the translation from Indonesian into English and to determine whether the meanings are preserved across both versions. AI was used to look for the data containing metaphorical expressions, but the result obtained was that not all sentences contained metaphorical expressions. The data consist of both sentences containing metaphorical expressions and without ones. The data were analyzed using a qualitative approach. The analysis is guided by the meaning in the translation framework proposed by Bowker (2023) and supported by Harris’s (2018) theory of metaphor. The finding is that the sentences without metaphorical expressions are translated with and without changes without significant loss of meaning. The metaphors are translated into metaphor-to-metaphor translation, metaphor-to-non-metaphor translation, and metaphor-to-simile translation.